Soil-lime reactions: the behaviour of a Brazilian red soil. - Barelli, N.; Melios, C. B.; Da Silva, R. C F (My University, 1986)
A red tropical soil was selected, with the main purpose of investigating how it reacted with calcitic and dolomitic limes, and which products are formed. Under normal (23-28oC) or slightly accelerated (40o and 60oC) conditions there is a rapid and substantial interaction between lime (calcitic or dolomitic) and the soil. The reactions take place in two steps, one before 7 g lime/100 g soil, and the other after 8 g lime/100 g of soil, either for calcitic or dolomitic lime. A morphologically discrete reaction product (tri-calcium aluminate hexahydrate) was found in the study, and in spite of the difference in morphology the product is shown to be the same by XRD for all compositions and T.-J.M.H.